Testing Different Properties of A Light-Cured Denture Base Material After Addition of Silicon Oxide Nanofiller (An in Vitro Study) - M Ali, Mohammed Moudhaffer (Journal of Baghdad College of Dentistry, 2017)
ABSTRACT Background: Improving the properties of heat- cured and self-cured acrylic resin have been studied by many researchers. However, little studies concerned with visible light cured resin (VLCR) improved through addition of nanofiller are available. The purpose of this study was to evaluate some properties of (VLCR) after addition of SiO2 nanofiller. Materials and Methods: SiO2 nanofiller were added to (VLCR) tray material after being dissolved in tetrahydrofuran (THF) solvent. According to the pilot study 2% SiO2 nanofiller addition exhibited better properties than the other percentages (1%, 3%). The main study conducted involved (100) specimens divided into 5 groups according to the test included. (20) Specimens were selected for each test (10 samples for the control group and 10 samples for the experimental 2% SiO2 nanofiller group). The properties investigated were transverse strength, impact strength, surface hardness, surface roughness, water sorption and solubility. Scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) were used to assess nanofiller distribution and identification of elements. The data were subjected to descriptive statistical analysis and independent sample t-test. Results: The mean value of transverse strength of experimental group increased significantly, while the impact strength of experimental group decreased significantly when compared to control group. A significant increase in surface hardness was noticed in the experimental group, while non-significant increase in surface roughness was observed. The water sorption values were decreased significantly, while a non-significant decrease in water solubility was observed in the experimental group. Conclusion: Addition of SiO2 nanofiller to (VLCR), slightly improve the transverse strength and surface hardness, while water sorption and solubility slightly decreased. The impact strength was significantly deteriorated, while the surface roughness shows non-significant increment.